Study and evaluation of indicators of relationships motor analyzer sportsmen of armsport - L.V. Podrigalo; M.N. Galashko; N.I. Galashko (Physical Education of Students)
The purpose of the article was to study and evaluate the relationship indicators of the functional state of the brush armsport athletes and those working at the amateur level. The results of measuring of tremor and assess the accuracy of the efforts of athletes. The study involved 29 people (20,79 + 0,77 years), divided into experimental and control groups. The fine coordination of hand muscles on the run-time test, the number of touches and squeezing on the wrist dynamometer given effort. Affirmed a lower level of physiological tremor in athletes. The data are interpreted as evidence of the importance of the functional state of the brush for effectiveness in armsport. It is shown that changes in physiological tremor can be used in the assessment of athletes. Application of the correlation matrix established affinity states surveyed.